Does school-based physical activity decrease overweight and obesity in children aged 6-9 years? A two-year non-randomized longitudinal intervention study in the Czech Republic - Sigmund Erik; El Ansari Walid; Sigmundová Dagmar (BMC, 2012)
Abstract Background Globally, efforts aimed at the prevention of childhood obesity have led to the implementation of a range of school-based interventions. This study assessed whether augmenting physical activity (PA) within the school setting resulted in increased daily PA and decreased overweight/obesity levels in 6-9-year-old children. Methods Across the first to third primary school years, PA of 84 girls and 92 boys was objectively monitored five times (each for seven successive days) using Yamax pedometer (step counts) and Caltrac accelerometer (activity energy expenditure AEE - kcal/kg per day). Four schools were selected to participate in the research (2 intervention, 2 controls), comprising intervention (43 girls, 45 boys) and control children (41 girls, 47 boys). The study was non-randomized and the intervention schools were selected on the basis of existing PA-conducive environment. Analyses of variance (ANOVA) for repeated measures examined the PA programme and gender effects on the step counts and AEE. Logistic regression (Enter method) determined the obesity and overweight occurrence prospect over the course of implementation of the PA intervention. Results There was a significant increase of school-based PA during schooldays in intervention children (from ≈ 1718 to ≈ 3247 steps per day; and from 2.1 to ≈ 3.6 Kcal/Kg per day) in comparison with the control children. Increased school-based PA of intervention children during schooldays contributed to them achieving >10,500 steps and >10.5 Kcal/Kg per school day across the 2 years of the study, and resulted in a stop of the decline in PA levels that is known to be associated with the increasing age of children. Increased school-based PA had also positive impact on leisure time PA of schooldays and on PA at weekends of intervention children. One year after the start of the PA intervention, the odds of being overweight or obese in the intervention children was almost three times lower than that of control children (p < 0.005), and these odds steadily decreased with the duration of the intervention. Conclusions The findings suggest that school-based PA (Physical Education lessons, PA during short breaks and longer recesses, PA at after-school nursery) in compatible active environments (child-friendly gym and school playground, corridors with movement and playing around corners and for games) has a vital role in obesity and overweight reduction among younger pupils.